Secagem intermitente de café (Coffea arabica L.) em secadores de fluxo cruzado e em secador experimental de camada fixa - Vieira, Gilmar (1994)
The present work investigated both the performance of intermitent vertical driers of cross flow, usually found in farms and drying characteristics in a experimental drier of fixed layer utilizing drying conditions similar to those of commercial driers. Driers presented variations in their internal physical characteristics such as the volume of the drying and tempering chambers, grain flow and air flow, which caused differences in the grains behavior during drying process. Some were difference observed in the drying process, occurring both among driers and within each one mainly with regard to drying temperature, that ranged from 40 to 80°C. In function of the physical, operational and also the raw-material, differences the drying time showed to be highly variable, from 50 to 96 hours of total utilization of the drier (drying and paralyzation) and from 23 to 57 hours of drying period alone. It was utilized during the experimental drying process a drier containing a drying chamber with 0,37m in diameter by 0,50m in height, heated through electrical resistences and air flow fed by a set of motor and fan. A constant temperature of 70°C, with a coffee" layer of 0,20m, air flows of 16,0, 33,0 and 63, Om-3 .min-1 .m-2, drying period of 30 and 60minutes, tempering period of 60 and 120 minutes, given a completely randomized experimental design in a factorial scheme (3x2x2) with three replications. A significant decreasing was noticed, both in the total time of drying and in the drying time it self, in function of the increasing of air flow. This decreasing was higher for shorter drying and tempering period ( 30 and 60 minutes respectively ). Drying times in the experimental drier were far shorter than in the mechanical intermitent drier of cross flow with variations of 8,6 to 20,8 hours.